(untitled) (diségno, 2020)
Along with his humanistic interests, Leon Battista Alberti (1404-1472) was attracted to the world of scientific knowledge both during his youth, while studying physics and mathematics, and when he definitively returned to Rome in 1443 following Pope Eugene IV (1383-1447) and started to study these subjects in greater detail [Bertolini 2004, pp. 246, 249]. It was while in Rome, that according to recent studies, historiography would erroneously place at 1450-1452, Alberti composed a manuscript in the vernacular entitled Ex Ludis Rerum Mathematicarum, better known as Ludi Matematici (read more).